Smart Energy Saving Lamp with Ambient Light Detection for Automatic Brightness Adjustment - Sukri, Muhammad Abdul Azim; Mohd Jamail, Nor Akmal; Kamarudin, Qamarul Ezani (Evolution in Electrical and Electronic Engineering, 2025)
This project aims to develop a smart energy-saving lamp that automatically adjusts its brightness based on ambient light levels, providing an energy-efficient lighting solution for residential and commercial spaces. The standard lighting systems operate at full strength hence consuming exorbitant amounts of surplus energy. While further, such actions decrease the lamp’s life. The proposed system integrates a Light Dependent Resistor (LDR) to sense ambient light intensity and an Arduino Uno microcontroller to process sensor data. An AC dimmer module was used for tuning the brightness level of a 220–240V dimmable LED lamp during system testing and calibration. The system is designed for relatively small rooms or office spaces, usually between 15 and 20 square meters. The recommended illumination level here is 500 lux. With minimum daylight, the lamp will be in full brightness. Increase in light level causes proportional dimming of the lamp so as to give adequate light and simultaneously save on energy cost. On the software level, an algorithm to control the brightness (easing out and in to the desired value in order to not produce sudden changes that could cause visual discomfort) has been used by the Arduino software. Tests and analysis show a potential energy saving up to 45%-50% with the proposed system in medium light conditions with respect to alternative light sources. The new system also can extend the lamp life by decreasing a thermal stress, while adjusting the brightness according to an actual light environment in real time. This project demonstrates the feasibility of adoption of smart control systems in lighting design in actual installations to conserve energy in residential and commercial buildings, and ensure sustainable development.